Analysis of Geometric and Hemodynamic Profiles in Rat Arteriovenous Fistula Following PDE5A Inhibition - Northrup, Hannah; Somarathna, Maheshika; Corless, Savanna; Falzon, Isabelle; Totenhagen, John; Lee, Timmy; Shiu, Yan-Ting (Frontiers in Bioengineering and Biotechnology, 2021)
Arteriovenous fistula (AVF) is essential for chronic kidney disease (CKD) patients on hemodialysis, but treatment for AVF maturation failure remains an unmet clinical need. Successful AVF remodeling occurs through sufficient lumen expansion to increase AVF blood flow and lumen area. Aberrant blood flow is thought to impair AVF remodeling, but previous literature has largely focused on hemodynamics averaged over the entire AVF or at a single location. We hypothesized that hemodynamics is heterogeneous, and thus any treatment’s effect size is heterogeneous in the AVF. To test our hypothesis, we used the PDE5A inhibitor sildenafil to treat AVFs in a rat model and performed magnetic resonance imaging (MRI) based computational fluid dynamics (CFD) to generate a detailed spatial profile of hemodynamics in AVFs. 90 mg/kg of sildenafil was administered to rats in their drinking water for 14 days. On day 14 femoral AVFs were created in rats and sildenafil treatment continued for another 21 days. 21 days post-AVF creation, rats underwent non-contrast MRI for CFD and geometrical analysis. Lumen cross-sectional area (CSA) and flow rate were used to quantify AVF remodeling. Parameters used to describe aberrant blood flow include velocity magnitude, wall shear stress (WSS), oscillatory shear index (OSI), and vorticity. Geometrical parameters include arterial-venous (A-V) distance, anastomosis angle, tortuosity, and nonplanarity angle magnitude. When averaged across the entire AVF, sildenafil treated rats had significantly higher CSA, flow rate, velocity, WSS, OSI, and vorticity than control rats. To analyze heterogeneity, the vein was separated into zones: 0-5, 5-10, 10-15, and 15-20 mm from the anastomosis. In both groups: (1) CSA increased from the 0-5 to 15-20 zone; (2) velocity, WSS, and vorticity were highest in the 0-5 zone and dropped significantly thereafter; and (3) OSI increased at the 5-10 zone and then decreased gradually. Thus, the effect size of sildenafil on AVF remodeling and the relationship between hemodynamics and AVF remodeling depend on location. There was no significant difference between control and sildenafil groups for the other geometric parameters. Rats tolerated sildenafil treatment well, and our results suggest that sildenafil may be a safe and effective therapy for AVF maturation.